Sheep and Cattle Are Not Susceptible to Experimental Inoculation with Hazara Orthonairovirus, a Tick-Borne Arbovirus Closely Related to CCHFV - Julia Hartlaub; Felicitas von Arnim; Christine Fast; Maryna Somova; Ali Mirazimi; Martin H. Groschup; Markus Keller (Microorganisms, 2020)
Hazara orthonairovirus (HAZV) is a tick-borne arbovirus closely related to Crimean–Congo hemorrhagic fever orthonairovirus (CCHFV). Whereas CCHFV is a biosafety level (BSL) 4 agent, HAZV is classified as BSL 2, as it is not known to cause any disease in humans. Belonging to the same serogroup as CCHFV, HAZV might act as a model which can provide a better understanding of this important zoonosis. Furthermore, the serological relatedness may cause diagnostic problems if antibodies against HAZV interfere with current CCHFV serological assays. Therefore, sheep and cattle—important natural hosts for CCHFV—were experimentally infected with HAZV to prove their susceptibility and evaluate potential antibody cross-reactivities. According to this study, neither sheep nor cattle are susceptible to experimental HAZV infections. Consequently, the HAZV infection in ruminants is clearly distinct from CCHFV infections. Sera of immunized animals weakly cross-reacted between HAZV and CCHFV in immunofluorescence and immunoblot assays, but not in commercial CCHFV ELISAs commonly used for field studies.